Absorption of twisted light by a mesoscopic atomic target. (3rd May 2016) - Peshkov, A A; Serbo, V G; Fritzsche, S; Surzhykov, A
Abstract: The excitation of a hydrogen-atom target by a twisted Bessel light beam is investigated. The atoms are assumed to have a Gaussian spatial distribution in the target. Theoretical analysis is performed within a nonrelativistic framework using a first-order perturbation approach and density matrix formalism. By using this theory, we derive the expressions for excitation cross sections and for alignment parameters of the excited atomic state. In particular, we make calculations for the 1 s → 2 p transition caused by the interaction of Bessel beams with the atomic target. For this transition, we analyze the population of magnetic sublevels for the excited 2 p state and study how it is affected by the projection of the total angular momentum of incident light. The calculations indicate that the projection of the total angular momentum of the incident Bessel beam affects the alignment of atoms for sufficiently small targets with size less than 200 nm. This can be observed experimentally by measuring the linear polarization of the subsequent fluorescent light.